2018
DOI: 10.1002/mma.4764
|View full text |Cite
|
Sign up to set email alerts
|

Multiset topology via DNA and RNA mutation

Abstract: Topology is the most important branch of modern mathematics, which plays an important role in applications. In this paper, we use the concept of the topology, based on the concept of multiset to solve an important problems in life (DNA and RNA mutation) to detect diseases and help biologists in the treatment of diseases. Also, we introduce a new theory that explains if there is an existence of a mutation or not, and we have a set of metric functions through which we examine the congruence and similarity and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…We must acknowledge that this subject has been studied by biologists as well as others. EI-Sharkasy and Badr [3], EI-Sharkasy et al [4] have shown that the notion of multiset topology plays a profound role to find the mutations of deoxyribonucleic acid (DNA) and ribonucleic acid (RNA). These articles demonstrate how a multiset topology can be used to identify diseases and assist biologists with disease diagnosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We must acknowledge that this subject has been studied by biologists as well as others. EI-Sharkasy and Badr [3], EI-Sharkasy et al [4] have shown that the notion of multiset topology plays a profound role to find the mutations of deoxyribonucleic acid (DNA) and ribonucleic acid (RNA). These articles demonstrate how a multiset topology can be used to identify diseases and assist biologists with disease diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Consider two M-topologies τ 1 and τ 2 on M as τ 1 = {M, ∅, {1/a}, {2/b}, {1/a, 2/b}} and τ 2 = {M, ∅}.Let N = {3/b}, then it is mixed (1, 2)-semi-open, but not a τ 1 -open mset. (ii) Let X = {a, b, c} and M = {2/a, 4/b, 1/c} ∈ [X]4 . Consider two M-topologies τ 1 and τ 2 on M as τ 1 = {M, ∅, {2/a}, {3/b}, {2/a, 3/b}} andτ 2 = {M, ∅, {1/b, 1/c}}.…”
mentioning
confidence: 99%
“…Recently, graphs, multisets, and rough sets have been used to represent structures such as the human heart [9] and medicine [10][11][12], which are useful in medicine, physics, and biology. Previously, we have used topology to study the similarity of DNA sequences and to identify mutations in genes, chromosomes, their locations, and amino acids that have changed [13]. We also used topology to study the recombination of DNA and to form a mathematical model for the recombination process [14].…”
Section: Introductionmentioning
confidence: 99%